Interdependent Hazards, Local Interactions, and the Return Decision of Recent Migrants - Govert Bijwaard; Christian Schluter (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
Consider the duration of stay of migrants in a host country. We propose a statistical model of locally interdependent hazards in order to examine whether interactions at the level of the neighbourhood are present and lead to social multipliers. To this end, we propose and study a new two-stage estimation strategy based on an inverted linear rank test statistic. Using a unique large administrative panel dataset for the population of recent labour immigrants to the Netherlands, we quantify the local social multipliers in several factual and counterfactual experiments, and demonstrate that these can be substantial.
Keywords: C41; C10; C31; J61; 330; interdependent hazards; local interaction; social multipliers; return migration